2018
DOI: 10.1007/978-3-319-78978-1_13
|View full text |Cite
|
Sign up to set email alerts
|

The Values of Self-tracking and Persuasive eCoaching According to Employees and Human Resource Advisors for a Workplace Stress Management Application: A Qualitative Study

Abstract: Self-tracking and automated persuasive eCoaching combined in a smartphone application may enhance stress management among employees at an early stage. For the application to be persuasive and create impact, we need to achieve a fit between the design and end-users' and important stakeholders' values. Semi-structured interviews were conducted among 8 employees and 8 human resource advisors to identify values of self-tracking, persuasive eCoaching, and preconditions (e.g., privacy and implementation) for a stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Consequently, interviews can have a broad range of goals. Examples include identifying points of improvement for a current situation such as treatment of forensic psychiatric patients [ 96 ]; analyzing target or risk groups in, for example, tick bites [ 100 ]; identifying points of improvement for prototypes or existing (eHealth) interventions according to end users or design experts [ 83 , 84 ]; identifying potential barriers and facilitators for implementation later in the process, such as high costs and required skills training [ 78 , 96 ]; describing a current behavior and its determinants [ 91 ]; collecting experiences of participants after letting them try out an app in real life [ 83 ]; and generating or validating values and requirements [ 15 , 28 , 98 , 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, interviews can have a broad range of goals. Examples include identifying points of improvement for a current situation such as treatment of forensic psychiatric patients [ 96 ]; analyzing target or risk groups in, for example, tick bites [ 100 ]; identifying points of improvement for prototypes or existing (eHealth) interventions according to end users or design experts [ 83 , 84 ]; identifying potential barriers and facilitators for implementation later in the process, such as high costs and required skills training [ 78 , 96 ]; describing a current behavior and its determinants [ 91 ]; collecting experiences of participants after letting them try out an app in real life [ 83 ]; and generating or validating values and requirements [ 15 , 28 , 98 , 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…2a, in which the values only mentioned by HR advisors are outlined. A more in-depth presentation of the results regarding the customer profile has been described elsewhere [41].…”
Section: Resultsmentioning
confidence: 99%
“…The prototype version of the Resilience Navigator app was developed based on the results of previously conducted research (Lentferink et al 2017(Lentferink et al , 2018(Lentferink et al , 2020) by some of the authors of this study (AL, HKE, HV, and LVG) during which we have followed the CeHRes roadmap (Centre for eHealth and Wellbeing research roadmap), a roadmap for the development of eHealth applications with a high focus on involving all important stakeholders and principles from business modelling (van Gemert-Pijnen et al 2011). A prototype version was used as this study is part of the development process of the Resilience Navigator app.…”
Section: Resilience Navigator Appmentioning
confidence: 99%
“…The prototype version of the Resilience Navigator app is developed following the CeHRes Roadmap, a roadmap for the development of eHealth with a high focus on involving all important stakeholders and the principles from business modelling (van Gemert-Pijnen et al 2011). Earlier research included a scoping review to identify critical success factors for self-tracking and persuasive eCoaching (Lentferink et al 2017) and a needs assessment among employees and HR advisors by means of interviews (Lentferink et al 2018) and focus groups among all identified key stakeholders using a business modelling approach (Lentferink et al 2020). The identified key stakeholders were employees, employers, representative councils within organisations, HR advisors, product owners, company doctors and business analysts (Lentferink et al 2020).…”
Section: Resilience Navigator Appmentioning
confidence: 99%